The application of MTA as apical plug for root canal obturation: In vitro study - Matović Ivan; Ilić Dragan V.; Petrović Renata; Ostojić Dejan (Serbian Medical Society - Dental Section, Belgrade, 2018)
Introduction Prognosis of endodontically treated tooth is directly correlated to the quality of apical obturation. Modern concept of endodontics in particular way points out the quality of apical filling. The aim of this study was to assess the quality of root canal obturation with MTA apical plug using the method of gas (argon) penetration. Material and Methods Sixty-six freshly extracted single rooted (single canal) teeth were divided into the two experimental (30 teeth) and one control group (6). All canals were instrumented using hand and rotary files in step-back technique and copious irrigation of 1%NaOCl. In the first experimental group teeth were obturated using different sealers: Gutta Flow (Roeko), AH Plus (DeTrey), Acroseal (Septodont) and mono gutta-percha cone (10 canals each). In the second experimental group obturation involved 3 mm of MTA-Angelus apical plug while the remaining canal space was filled with the same three sealers as in the first group. The rate of gas permeability by Leak detector-Edwards LD 416 was measured in all teeth. Results The best seal was found in teeth obturated with Gutta Flow and MTA plug with average diffusion rate of 264.4 sec while the worst quality of obturation was found with Acroseal (178.5 sec-the highest gas permeability). All samples with MTA plug exhibited significantly lower leakage than the samples filled without MTA apical plug. Conclusion Root canals filled with MTA apical plug exhibited statistically significant lower gas permeability in comparison to the ones filled with sealer and guttapercha cones only.